On the possibility of generation of few-cycle 1.8 μm pulses based on SRS in hydrogen. (3rd November 2021) - Didenko, N V; Losev, L L; Pazyuk, V S
Abstract: Stokes pulses with a spectrum corresponding to 16 fs transform-limited pulse were generated at stimulated Raman scattering (SRS) of 400 fs ytterbium laser pulses in fused silica capillary filled with hydrogen. Stokes pulses were compressed to 20 fs. The energy conversion efficiency reached 12%.